The Ipiranga museum and its educational accessibility as a museum with a digital collection - Carvalho, Aline Lisangela da Silva Galvani [UNESP]; Paulino, Ana Elisa Lara [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Arquitetura Artes & Comun, 2024)
Over the last two decades, physical museums have invested in communication strategies to make Brazilian cultural collections available to the public on the web. With this in mind, this article presents some of the actions taken by the Ipiranga Museum to provide educational accessibility through its digital collection. Studies in the field of communication, which will be explored below, show the museum's institutional concern beyond conserving, preserving and safeguarding museum assets. By providing access to the digital collection, the Ipiranga Museum not only contributes to the inclusion and democratization of culture, but also reinforces its educational commitment to society.
Keywords: Digital collection; accessibility; communication; education; Ipiranga Museum